Vertical accretion and carbon burial rates in subtropical seagrass meadows increased following anthropogenic pressure from European colonisation. (5th March 2018) - Samper-Villarreal, Jimena; Mumby, Peter J.; Saunders, Megan I.; Barry, Linda A.; Zawadzki, Atun; Heijnis, Henk; Morelli, Guia; Lovelock, Catherine E.
Abstract: Seagrass meadows serve as marine carbon sinks, though rates of carbon burial and sediment accretion may vary within and among seagrass meadows due to spatial and temporal variability in sedimentary and biophysical conditions. However, few data are available to evaluate variation in carbon burial over decades to centuries, particularly in subtropical seagrass meadows. Here we assess historical trends in rates of vertical accretion and carbon burial in subtropical seagrass sediments in Moreton Bay, Australia. A total of 19 sediment cores varying in length from 22 to 205 cm were collected from six locations, including two locations where seagrass meadows occurred historically but were lost in recent decades. Cores were dated using 210 Pb and 14 C. Geochronologies were modelled based on the successful 210 Pb dates for two of the locations combined with 14 C at five locations. Organic and inorganic carbon content, dry bulk density and stable carbon and nitrogen isotope composition (δ 13 Corg, δ 15 N) were measured throughout the cores. Sediments underlying seagrass meadows in Moreton Bay have organic carbon stored up to a depth of at least 2 m which dates to over 7000 yr BP. Across the entire time series, organic carbon burial rates averaged 19 g m −2 yr −1 and inorganic carbon burial rates averaged 27 g m −2 yr −1 . Overall mean rates of vertical accretion were estimated to be 0.2 cm yr −1 . Rates of vertical accretion accelerated 10-fold following European colonisation which commenced in 1824, from 0.06 ± 0.06 cm yr −1 to 0.66 ± 1.19 cm yr −1 . Similarly, rates of organic carbon burial averaged 7.2 ± 5.5 g m −2 yr −1 but then increased 7-fold post-colonisation to 50.5 ± 82.1 g m −2 yr −1 . Thus, in Moreton Bay, European settlement and associated land-use change has enhanced sediment accretion and carbon burial in seagrass sediments.